VDAC‐2: Mitochondrial outer membrane regulator masquerading as a channel?. (13th January 2016) - Maurya, Svetlana Rajkumar; Mahalakshmi, Radhakrishnan
Abstract : The voltage‐dependent anion channels (VDACs) are the workforce of mitochondrial transport and as such are required for cellular metabolism. The elaborate interplay between mitochondria and the apoptotic pathway supports a role for VDACs as a major regulator of cell death. Although VDAC‐1 has an established role in apoptosis and cell homeostasis, the role of VDAC‐2 has been controversial. In humans, VDAC‐2 is best known for its anti‐apoptotic properties. In this Viewpoint, we associate the various functional studies on VDAC‐2 with structural reports, to decode its unique behavior. The well‐structured N‐terminus, compact barrel form, differences in the loop regions, specific transmembrane segments and the abundance of thiols in VDAC‐2 enable this isoform to perform a different subset of regulatory functions, establish anti‐apoptotic features and contribute to gametogenesis. VDAC‐2 structural features that demarcate it from VDAC‐1 suggest that this particular isoform is better suited for regulating reactive oxygen species, steroidogenesis and mitochondria‐associated endoplasmic reticulum membrane regulatory pathways, with ion transport forming a secondary role. A better understanding of the unique structural features of the VDAC family will aid in the design of inhibitors that could alleviate irregularities in VDAC‐controlled pathways. Abstract : In this review, we associate the various functional studies on voltage‐dependent anion channel isoform‐2 (VDAC‐2) with structural reports, to decode its unique behavior. The well‐structured N‐terminus, compact barrel form, differences in the loop regions, specific transmembrane segments and the abundance of thiols in VDAC‐2 enable this isoform to perform a different subset of regulatory functions when compared to VDAC‐1, establish anti‐apoptotic features and contribute to gametogenesis.